PSYCHOLOGICAL DISORDERS OF CHILDREN : A BEHAVIORAL APPROACH TO THEORY, RESEARCH AND THERAPY - ROSS, ALAN O. (MC GRAW HILL BOOK COMPANY NEW YORK, 1974)
This book was written to fill the need for a behaviorally oriented presentation of psychological disorders of children and of their treatment through behavior therapy.
Keywords: CHILD AND ADOLESCENT DEVELOPMENT